Foreign trade transactions of a chosen company - Šutová, Linda (2017)
This thesis focuses on the foreign trade transactions. The goal is to analyze the business of the chosen company and to summarize the differences between inland and foreign transactions. The partial goal is to evaluate the activity of the chosen company and to point out opportunities for improvement. The general context of the goods and services trade is discussed in the theoretical part of the thesis. It involves services that are necessary to run the trade, delivery terms, Intrastat and customs duty. The practical part deals with general characteristics of the trade of the chosen company. Then, it analyses particular business cases and shows the differences between inland and foreign transactions. Furthermore, the mistakes of the transactions are analyzed and the correct interpretation is shown from the accounting and the tax point of view.